Studi Karakteristik Air-Tanah di Kawasan Nuklir Pasar Jumat (KNPJ) dengan Metode Hidrokimia dan Isotop Alam - Sanusi, Neneng Laksminingpuri; Nurfadhlini; Satrio (EKSPLORIUM, 2018)
Groundwater research has been conducted in Nuclear Area of Pasar Jumat (KNPJ) using hydrochemical data and natural isotopes methods. The research was conducted by taking a number of water samples in some areas of KNPJ and also its surrounding areas. The water samples were then analyzed its hydrochemical concentration (anion-cation) and natural isotope concentration d2H and d18O using lasser counter device. Water chemical analysis was conducted by using ion chromatography and titration methods. The purpose of this research is to know the characteristics of groundwater to the possibility of its interaction with the surrounding surface water. Based on the results of hydrochemical analysis (anion-cation) and natural isotopes (d2H, d18O) indicates that groundwater still reflects the character as fresh groundwater or freshwater. The deep aquifer groundwater is also indicated to be unrelated to groundwater of shallow aquifers located above it. While most shallow groundwater still show the character of fresh groundwater, and some others namely SB-8, SB-9, and SB-10, the groundwater undergo ion exchanges and interact with surface water. Surface water for SB-8 is estimated come from the seepage of the liquid plant fertilizer, whereas for SB-9 and SB-10 surface water is estimated come from septic tank seepage.